An investigation on the potential of mud as sustainable building material in the context of Kerala. (2017) - Lekshmi, M.S.; Vishnudas, Subha; Nair, Deepa G.
A house is made of building blocks but a home is made of hearts. In today's busy world, everybody is striving hard to make both ends meet in having a suitable and sustainable shelter for a healthy living. In the past few decades, cement and concrete have conquered the construction industry to such an extent that common man has forgotten to think of any alternative natural building material. On one side world is facing serious issues regarding carbon emissions, health issues generated from improper waste disposal while on the other side it is giving way to marvellous sky scrapers made of non-eco-friendly materials. Kerala has been always mentioned as God's own country for years, but the same credit can be truly achieved only if Keralites also practise building construction based on natural materials like mud that are sustainable to our environment. This paper is an attempt to investigate the potential of mud as a sustainable material in the context of Kerala.